The gap between the management and success of elite middle and long distance runners in Kenya - Kanyiba, L. R.; Mwisukha, A.; Onywera, V. O. (African Journal for Physical, Health Education, Recreation and Dance, 2015)
Kenya has been very successful at middle and long distance races in international competitions for the last five decades. However, Kenyan world record beaters have denounced the motherland flag by switching nationality, sought training in alien bases under foreign managers, been living under deplorable conditions after athletic career, or they have been the victim of neglect-induced death at a prime career age. There is extensive research available on the success of Kenyan athletes, but no study to the knowledge of the researchers has linked the management of Kenyan athletes to that success. As a foundation for further research, the current exploratory study was designed to determine whether elite athletes, their coaches, and administrative officials (Athletics Kenya [AK] officials) differed on the effectiveness of the sampled managerial practices (personnel, equipment/facilities, motivation, patriotism, team selection, and training programs) in facilitating the success of Kenyan elite runners. The study further details the effect of nationality change and the role of foreign managers towards the success of Kenyans in distance running. The study took place in Nairobi, Kenya. The sample comprised 185 elite athletes, 49 coaches, and 34 AK officials. The Chi-square (X2) test for independence (a = .05.) analysis was used to determine a consistent and predictable relationship between the variables. The pairwise comparisons showed that athletes differed significantly with coaches and AK officials on the sampled managerial practices while coaches did not differ significantly with AK officials. Suggestions for further research are given.